Expressions of Violence against Women in French Novel Syngué Sabour and the Indonesian Translation - Arrasyid, Noor Diana; Sajarwa, Sajarwa (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
Abstract Violence against women is a gender issue that often appears in literary works. In cases where those works become translated, this theme may experience shifts in context from the source text to the target text, which can cause a shift in meaning as well. This research aims to discern how expressions of violence against women as narrated in a source text become translated into the target text. In this qualitative descriptive study, data in the forms of words, phrases, or sentences denoting violence against women have been taken from the French novel Syngué Sabour and its Indonesian translation, Batu Kesabaran. The results show that the expressions related to verbal and sexual violence were translated by means of overlexicalization. The translator employed this strategy to place emphasis on the problems raised, although the results give the impression that the translator portrays women in an exceedingly inferior and negative manner. On the other hand, expressions related to physical violence, murder, and human trafficking tend to use a more neutral language. This is true since the issue of violence against women in literary works can be seen not only through the chosen diction but also through the characters’ actions and behaviors.